Elemen Kecerdasan Wirausaha Untuk Meningkatkan Kinerja Industri Kecil dan Menengah (IKM) di Surabaya - Rudi Santoso; Candraningrat Candraningrat; Lilis Binawati (BISMA (Bisnis dan Manajemen), 2017)
The aims of this study is to know the influence of the four intelligences as independent variables on the performance of Small and medium Industries (SMIs) in Surabaya Indonesia. The population of this research is SMEs in Surabaya, Indonesia which build by Department of Industry and Trade, Surabaya. The samples of this research is 100 small and medium industries. Analysis method used multiple regression analysis. The result of coefficient determination (R2) shows that the influence of all variables which are Spiritual Intelligence, Financial Intelligence, Emotional Intelligence dan Social Intelligence have contributed 56,7% to performance. While the other 43.3% contributed by another variable which is not discussed in this study. The hypothesis test shows that as simultaneously these 4 (four) variable shave significantly affect to the performance of SMEs, but as partially by t-test shows that Financial Intelligence and Emotional Intelligence and Social Intelligence have significantly affected to performance but Spiritual Intelligence have no significant effect on Performance of SMEs in Surabaya. Limitation of this study is to use a small research sample. In addition, the scope of the study area is too narrow, which is limited to Surabaya. Therefore, further research can be developed from the side of the number of samples used and the wider coverage area. The practical implications of this research are useful for IKM development in Surabaya. This development is done through 3 elements of entrepreneurial intelligence that is financial intelligence, social intelligence, and emotional intelligence. The three main elements are further developed with the aim that IKM in Surabaya will be more sustainable